1988
DOI: 10.1200/jco.1988.6.9.1411
|View full text |Cite
|
Sign up to set email alerts
|

High-dose chemotherapy with autologous bone marrow transplantation in 50 advanced resistant Hodgkin's disease patients: an Italian study group report.

Abstract: Fifty patients with recurrent Hodgkin's disease have been treated with high-dose therapy followed by autologous bone marrow transplantation. Forty-one patients had extranodal sites of relapse and 31 patients had constitutional symptoms. Two patients had been treated with mechlorethamine, vincristine, procarbazine, and prednisone (MOPP), lomustine, vinblastine, procarbazine, and prednisone (CcVPP), and radiation; 16 patients with MOPP, doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD), radiation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0
1

Year Published

1990
1990
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(24 citation statements)
references
References 13 publications
0
23
0
1
Order By: Relevance
“…Jones et al (1990) reported their series of 50 patients which included 21 patients treated with an allograft and found that a complete or partial remission at the time of transplant was not a significant prognastic factor, but the presence of sensitive disease at the time of transplantation was a favourable prognostic sign for surviving event-free. The efficacy of high-dose chemotherapy with bone marrow rescue has been shown to be greater when there is some degree of sensitivity to the therapy (Lohri et al, 1991;Carella et al, 1988;Jagannath et al, 1989) Lohri et al (1991) also reported a very strong negative impact on outcome in patients with stage IV disease at presentation, recurrence within a year of primary treatment or presence of B symptoms ar recurrence. We did not find any of these factors to be significant in our study as most have been employed to predict response to second line therapy whereas most of our patients were at different stages in their disease, usually much later when the duration of first response may not have been relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Jones et al (1990) reported their series of 50 patients which included 21 patients treated with an allograft and found that a complete or partial remission at the time of transplant was not a significant prognastic factor, but the presence of sensitive disease at the time of transplantation was a favourable prognostic sign for surviving event-free. The efficacy of high-dose chemotherapy with bone marrow rescue has been shown to be greater when there is some degree of sensitivity to the therapy (Lohri et al, 1991;Carella et al, 1988;Jagannath et al, 1989) Lohri et al (1991) also reported a very strong negative impact on outcome in patients with stage IV disease at presentation, recurrence within a year of primary treatment or presence of B symptoms ar recurrence. We did not find any of these factors to be significant in our study as most have been employed to predict response to second line therapy whereas most of our patients were at different stages in their disease, usually much later when the duration of first response may not have been relevant.…”
Section: Discussionmentioning
confidence: 99%
“…The Bu/Mel/T regimen evaluated in our study demonstrated a comparable efficacy to the TBI-based and non-TBI-based regimens previously reported. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]40,41 In the current series, patients with more advanced disease or had received prior DLRT, who had an outcome expected to be poor, had an EFS of 33 and 36% at 5 years, respectively, after the Bu/Mel/T regimen. It was not possible to directly compare the outcome of these patients to the TBI-based regimen since prior DLRT is generally an exclusion for TBI.…”
Section: Discussionmentioning
confidence: 99%
“…1 High-dose chemotherapy with or without radiation therapy supported with autologous stem cell transplantation (HDC/ASCT) is potentially curative for this subset of patients. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Total body irradiation (TBI) in combination with high-dose cyclophosphamide (CY) (TBI/ CY) 3,4 and etoposide (TBI/CY/E), 5,6 , and the combination of CY, carmustine and etoposide (CVB), 5,6,9,10,[12][13][14][15][16] carmustine, etoposide, cytosine arabinoside with either melphalan (BEAM) 18,19 or cyclophosphamide (BEAC) 20 constitute the most common high-dose regimens evaluated. The superiority of a specific regimen, however, has not been demonstrated.…”
mentioning
confidence: 99%
“…The initial chemosensitivity to salvage chemotherapy remained the most important prognostic factor. [10][11][12] The proportion of patients salvaged by HDT ϩ ASCT reached 45-60% in patients with good prognostic features according to the prognostic model proposed by Vose et al 13 for NHL patients and by Brice et al 14 for those with HD. However, for patients with adverse prognostic factors, the probability of being cured decreases rapidly to under 40% with standard conditioning regimen and ASCT.…”
mentioning
confidence: 99%